COMPARISON OF ROPIVACAINE ALONE VS ROPIVACAINE WITH METHYLPREDNISOLONE INJECTION AS A TREATMENT OF TRIGGER POINTS FOR MYOFASCIAL PAIN: A SUPERIORITY RANDOMIZED CLINICAL TRIAL - MUSHTAQ , S; BHATTI , KM; NAWAZ , Q; BASHIR , K; GHAFOOR , AUR (Biological and Clinical Sciences Research Journal, 2024)
Soft tissue rheumatism, known as myofascial pain syndrome (MPS), is typified by taut bands, transferred pain that is distinct, sensory alterations that occur, and a local twitch response. It is also connected with trigger points in one or more muscles. The purpose of the research is to evaluate the effects of injections of Ropivacaine alone vs. Ropivacaine with methylprednisolone in decreasing pain in people in our community who have myofascial pain caused by trigger points. The design of this study was a randomized controlled trial. This study was carried out from July 2022 to August 2023. The research comprised 50 individuals (27 females and 23 males) diagnosed with MPS who came to our clinic. Using online randomization software, the patients were randomly divided into two groups. Group B got a mixture of 0.25% Ropivacaine & 10mg methylprednisolone in 3ml normal saline at each trigger point, whereas Group A received 3ml of 0.25% Ropivacaine. Dry needling of trigger sites was done in both groups. Patients were assessed at two, four, and eight weeks of intervention. The patients' pre-treatment assessment measures showed no statistically significant differences. After 4 and 8 weeks of assessment, Group B NRS pain and BDI scores showed statistically significant improvements compared to pre-treatment results (p<0.05). NRS and BDI scores were reduced in group A compared to their pretreatment values, but that was not clinically significant. Results of our study showed that there was a statistically significant difference between both groups in terms of pain, stress, and anxiety after the intervention. Ropivacaine with methylprednisolone gave better results than Ropivacaine alone in reducing pain and anxiety among the study population.